Strengthening Financial Literacy and Inclusion in Islamic Cooperatives Through Mentorship and Counseling in Indonesia - Dadang Husen Sobana; Deni Kamaludin Yusup; Vemy Suci Asih; Elsa Yulandri; Fauzi Zulfikar Ahmad (Journal of Islamic Economics and Business, 2024)
West Java has a higher Sharia financial inclusion index than the national financial inclusion index, but this is not followed by the Islamic literacy index. This study aims to measure the increase in Islamic financial literacy and inclusion in the Islamic cooperative sector (BMT/KSPPS) before and after mentoring and counseling programs related to Islamic financial inclusion and literacy in West Java communities. The method used in this study is the Community-Based Participatory Research (CBPR) Method. The type of data used is primary data, which is obtained from the results of questionnaires and interviews in the field. The objects of service are categorized into two, namely mentoring programs for administrators and members of the BMT Al Muhsinin KSPPS, and community extension programs, and members of the ta'lim council in the BMT Al Muhsinin area. The data analysis technique uses a paired sample t-test difference test, with pre and post-test data related to Islamic financial literacy and inclusion. The results showed that there were significant differences before and after the mentoring and counseling. The four clusters carried out by mentoring and counseling began to understand more deeply important aspects of Islamic cooperatives such as the role of the Islamic supervisory board, the sales and purchase contracts used, daily practices, and profit-sharing ratios. With enhanced understanding, cooperative members and the general public have better access to Islamic financial services, which in turn can improve their economic well-being and support local economic development.